Protein diversity in discrete structures at the distal tip of the trypanosome flagellum - Varga, V; Moreira-Leite, F; Portman, N; Gull, K (National Academy of Sciences, 2017)
The distal end of the eukaryotic flagellum/cilium is important for axonemal growth and signaling and has distinct biomechanical properties. Specific flagellum tip structures exist, yet their composition, dynamics, and functions are largely unknown. We used biochemical approaches to identify seven constituents of the flagella connector at the tip of an assembling trypanosome flagellum and three constituents of the axonemal capping structure at the tips of both assembling and mature flagella. Both tip structures contain evolutionarily conserved as well as kinetoplastid-specific proteins, and component assembly into the structures occurs very early during flagellum extension. Localization and functional studies reveal that the flagella connector membrane junction is attached to the tips of extending microtubules of the assembling flagellum by a kinesin-15 family member. On the opposite side, a kinetoplastid-specific kinesin facilitates attachment of the junction to the microtubules in the mature flagellum. Functional studies also suggest roles of several other components and the definition of subdomains in the tip structures.